The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.3345/kjp.2010.53.12.1012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of transcatheter closure of patent ductus arteriosus in small children weighing 10 kg or less

Abstract: PurposeTranscatheter closure has become an effective therapy in most patients with patent ductus arteriosus (PDA). However, there are difficulties in transcatheter closure of PDA in small children. We reviewed clinical outcomes of transcatheter closure of PDA in children weighing less than 10 kg in a single center.MethodsBetween January 2003 and December 2009, 314 patients with PDA underwent transcatheter closure in our institute. Among them, 115 weighed less than 10 kg. All of these patients underwent transca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
(27 reference statements)
3
16
1
1
Order By: Relevance
“…No pathology developed at any later stage. This confirms the result of a smaller study of Park et al . Interestingly, Sreeram et al suggested that the use of echocardiogram was an unreliable screening method for decreased flow in left pulmonary artery, and that its stenosis is a rare complication especially with the use of multiple coils .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…No pathology developed at any later stage. This confirms the result of a smaller study of Park et al . Interestingly, Sreeram et al suggested that the use of echocardiogram was an unreliable screening method for decreased flow in left pulmonary artery, and that its stenosis is a rare complication especially with the use of multiple coils .…”
Section: Discussionsupporting
confidence: 77%
“…Percutaneous occlusion of a patent ductus arteriosus (PDA) with coils or occlusive devices is effective and the method of choice outside the neonatal period . Potential adverse effects of the intervention include device‐related obstruction to flow in the left or right pulmonary arteries or descending aorta, persistent shunting past the device with potential subsequent haemolysis, and device migration.…”
Section: Introductionmentioning
confidence: 99%
“…We used Amplatzer Duct Occluder (ADOI) in 11 cases, Amplatzer duct Occluder (ADOII) in 4 cases and only one PDA was closed with Amplatzer Duct Occluder (ADOIIAS). The results documented in our series are in accordance with theresults reported by other interventional paediatric cardiac centres [6,[17][18][19]22].…”
Section: Original Research Articlesupporting
confidence: 92%
“…Pediatric Review: International Journal of Pediatric Research Available online at: www.medresearch.in 250|P a g e closure of PDA in children weighing 5 kg or less. In a previous report by Park et al [17], the median age of 115 patients was 8 months and mean body weight was 7.8kg while in our study median age was 6 months and median weight was 3.2 kg.…”
Section: Original Research Articlecontrasting
confidence: 48%
“…Transcatheter closure procedures have been performed with high success rates both in children and adults [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Due to advances in diagnostic and therapeutic modalities diagnosis and treatment of PDA can be accomplished at a relatively early age [5][6][7] .…”
Section: Discussionmentioning
confidence: 99%